Socialization of the Geological Heritage (Geoheritage) of the Proposed Plan for the Bone Geopark of South Sulawesi - Asri Jaya; Fauzi Arifin; Kaharuddin Kaharuddin; Busthan Azikin; Hamid Umar; Musri Ma'waleda; Ulva Ria Irfan; Adi Tonggiroh; Ilham Alimuddin; Sahabuddin Jamadil; Baso Rezki Maulana; Muhammad Sulhuzair Burhanuddin; Kifayatul Khair Masyhuda Zulkifli; Adi Adi (Faculty of Engineering UNHAS, 2023)
The development of a geopark in the region should be initiated by the determination of geoheritage collected from the geological diversity inventory. The geoheritage initiation and preparation should be involved the educational institutions, we have assisted stakeholders of Bone Regency through the university community services (PkM) program in the form of the socialization of geoheritage in order to prepare and proposed Bone Geopark of South Sulawesi. To get an initial baseline of the geoheritage potential of Bone Regency and to measure participants' abilities, it begins with an FGD and a pre-test assessment, the results of the first FGD and pre-test activities showed that in general stakeholders have limited knowledge of the preparing document, characterization, and inventory of geoheritage, and geoheritage assessment. We have mentored geoheritage characterization, geodiversity inventory, and geoheritage assessment as problem-solving, which were conducted through surveys, desk study, and geoheritage assessment value methods. At the end of the activity returned to conduct FGD and post-test with involved all of the stakeholders. The results of the socialization program show a significant increase in the understanding of participants, especially the PERWIRA La Patau's was an increase of 28.5% (from 31.5% to 70%). Whereas representatives of the government, education institutions, and other non-government organizations still have limited understanding, increasing by 19.5% (from 17.0% to 36.5%). We still further proposed socialization and mentoring to prepare and propose geoheritage in the future. The geodiversity and landscape characteristics of the Bone regency can be divided into three morphology domains, namely: 1) The western part is demonstrated by the morphology domain of the highland of the volcanic complex that consists of non-volcanic, caldera, tower karst landscape features, 2) The central part is demonstrated by morphology domain of the Walanae valley that consisting of Walanae Depression and Walanae fault escarpment landscape features, 3) The eastern part is demonstrated by morphology domain of the Walanae structural lineament, the Kalamiseng volcano, the Taccipi cone karst and coastal line of the Bone Gulf landscape features. The results of the geodiversity inventory and geoheritage assessment of Bone Regency generally have suggested high scientific and educational values, moderate tourism potential, and low degradation potential. We concluded that this area has geodiversity potential and deserves to be submitted its geoheritage to the government.